Desarrollo lógico matemático en niños de Educación Inicial de la Unidad Educativa ¨Belisario Quevedo¨ - Sangopanta Guilcamaygua, Katherine Paulina (2023)
In the present project entitled "Mathematical logical development in children of initial education of the Belisario Quevedo Educational Unit" it was oriented to solve the following problem: The lack of execution of adequate exercises for the mathematical logical development in the mentioned educational institution and it was determined as Objective: Diagnose the mathematical logical development of the children of the initial level of the Educational Unit "Belisario Quevedo". The qualitative approach was used with the interview and the observation; For its concretion, the information gathering instruments were used, the observation sheet addressed to the children of the initial level and the question guide was used in the interview with the teacher of the institution, which allowed us to conclude that, most of the Students are in the process of developing Logical-Mathematical thinking skills, in addition, one of the most common causes that affect logical-mathematical development is that initial level students lack motivation to learn and develop thinking skills such as information organization. , problem solving and decision making, which help to solve the daily problems that we face every day, therefore, the need arises to propose recommendations to solve the problem, oriented to the preparation of teachers in methodological strategies for the mathematical logical development.